IS COST COMPETITIVENESS A SUFFICIENT DRIVING FORCE FOR CROATIAN EXPORTS? (The South East European Journal of Economics and Business, 2025)
This paper examines the extent to which Croatia relies on a cost-based export strategy by analyzing the link between cost competitiveness, measured by unit labor cost (ULC) and exports of manufacturing firms from 2002 to 2022. Using a panel first-differences OLS approach, the study finds that cost competitiveness significantly shapes export activity of firms of all sizes and technological intensities, but with considerable heterogeneity. The results show a non-linear relationship between ULC and exports that is not asymmetrical. The relationship is  weaker for firms with lower export intensity and for high‐tech firms. Higher ULC is associated with greater export sensitivity and lower productivity, confirming that export sensitivity is lower for more productive firms. In the future, a further strengthening of the link between costs and exports can be expected, i.e. exports will react more sensitively to cost fluctuations. As a result, price and cost stability will become even more crucial. Overall, this analysis provides the most comprehensive study to date on how cost factors affect Croatian merchandise exports, implying that boosting product quality and productivity can reduce cost pressures and promote long-term competitiveness.